A novel polypeptide vaccine and adjuvant formulation of EV71. Issue 9 (20th December 2021) - Liu, Zhiang; Yang, Yunfan; Meng, ChenChen; Fan, Meihua; Guo, Jing; Li, Jie; Jing, Zepeng; Wang, Pingping; Li, Ruipeng; Feng, Zhiwei; Ren, Feng; Wang, Mingyong; et al.
ABSTRACT: Hand foot and mouth disease (HFMD) is an infectious disease mainly caused by Enterovirus 71 (EV 71). However, the effective treatment is limited currently. The aim of this study was to investigate the activity of the vaccine including the EV71 polypeptides mixed with a novel adjuvant containing CpG oligodeoxynucleotides (CpG ODNs). After collecting mouse sera, we determined the antibody concentration in serum by enzyme-linked immunosorbent assays (ELISA). Then, CD19 + CD27 + B cells in the spleen were analysed by flow cytometry. The assay revealed that a substantial increase in antibody titers was achieved. This indicates a high level of immunogenicity for peptide vaccine and the good stability of adjuvant, also suggests that the combination of vaccine and adjuvant can stimulate the production of high-level antibodies and CD19 + CD27 + B lymphocytes in mice. Furthermore, the antibody could effectively identify EV71 inactivated virus. The results demonstrated that the autonomous construction of EV71 polypeptide vaccine had a good immunogenicity. Moreover, the peptide vaccine injection with a novel adjuvant, which is easy to prepare, could cause a high antibody level of EV71 and shown a good application prospect. Abstract : The self-designed polypeptide vaccine effectively produces antibodies against EV71 and plays an antiviral role.